Komunikasi Pembangunan sebagai Model Pemberdayaan di Taman Wisata Bur Telege Aceh Tengah - Sa'adah, Nur; Bungsu, Agung Pangeran (LUGAS Jurnal Komunikasi, 2024)
Participatory development communication is a communication model that is adaptive to various social conditions of the community. One of them is the Bur Telege tourist park located in Hakim Bale Bujang village, Takengon city, Central Aceh. Bur Telege was established due to the local community's concerns about the high level of violations of Islamic law that occurred, the second reason being the difficulty of finding employment at this time. An interesting thing to study is of course because the Bur Telege tourist park is managed directly by the Village-Owned Enterprise BUMD which works together to find the best solution to the problems faced. This study will try to review how development communication is used to empower the local community. Four pillars were found until finally the empowerment model used can be stimulated. Starting from the preparation of the vision and mission of the Bur Telege tourist park, then continued with a common perception, promotion, education and motivation, then continued with the institutionalization stage, then entered the support mobilization stage and finally the action stage.